فعالية الطريقة الصوتية لتعليم مهارة القراءة للتلاميذ في المدرسة محمدية 9 الإبتدائية مالانج - Fakhira, Farha (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
Comprehension and mastery of phonology contributes greatly to reading skill. With good understanding and eloquent pronunciation, a person can establish what he is saying to the addressee. If phonology does this skill with eloquence, it will affect the listener, because the information will be obtained by its clear transmission. The task area is to understand phonology influencing reading skill. Reading skill cannot be fully mastered if science understands the sounds a little. As well as learning science, sounds are very important to learn in the Arabic language. Research Objectives In this study, the research is to find out the effectiveness of the phonological method in the reading skill of pupils in the primary school Muhammadiyah 9 Malang. In this study, the researcher used the experimental method with the quantitative approach, and the type of this research is real experimental. It includes two groups, the experimental group and the control group. Research tools including observation, test, and questionnaire. The data collection method is Statistic Descriptif and SPSS. Data analysis using a t-test. The result of this research study is that the use of phonetic method in teaching reading skill in Muhammadiyah 9 Elementary School Malang is effective. Evidence that the statistical result = 15.14 is greater than the result of the significant estimate 5% = 1.67, meaning that Ha is acceptable or that the hypotheses of this research are acceptable.